Bioaccumulation of metals and biomarkers of environmental stress in Parablennius sanguinolentus (Pallas, 1814) sampled along the Italian coast. Issue 1 (15th September 2017) - Ferrante, Margherita; Pappalardo, Anna Maria; Ferrito, Venera; Pulvirenti, Valentina; Fruciano, Carmelo; Grasso, Alfina; Sciacca, Salvatore; Tigano, Concetta; Copat, Chiara
Abstract: Heavy metal pollution is one of the greatest threats to the ecosystems because it degrades the habitat and is potentially toxic to wildlife and human populations. In the last few decades, bioaccumulation studies performed with a multimarker approach have been a valuable tool for the investigation of environmental and animal safety. We perform an analysis of a benthic teleost fish species – Parablennius sanguinolentus – sampled at several Italian coastal sites with different degrees of anthropogenic pressure. Our integrative analysis encompasses bioaccumulation of 10 metals, biomarkers of environmental stress (micronuclei and nuclear abnormalities) and neutral genetic variation (using sequences of the mtDNA control region). We find a clear and significant correlation of metal bioaccumulation with micronuclei and nuclear abnormalities, especially with undisputed genotoxic metals, such as Cd, Cr, Hg and Pb. Furthermore, the molecular genetic analysis revealed a decrease of genetic variability in the populations more subjected to anthropic pressure. Highlights: Bioaccumulation of metals and biomarkers of environmental stress was studied. P . sanguinolentus was sampled in 8 sites of Italian coastal water. Pollution degree was strongly correlated with micronuclei and nuclear abnormalities. Genetic variability was strongly reduced in more contaminated sites.